Behavior of parents and children in the way they use public transport. A case study of Iranian households. Issue 1 (March 2022) - Ehteshamrad, Shideh; Saffarzadeh, Mahmood; Mamdoohi, Amirreza; Nordfjærn, Trond
Highlights: Both school and work trips were considered in a joint model. Parents adjust to children's requirements, compromising on their own situation. Individuals are more sensitive to social pressure than self-evaluation. Psychological, habitual, situational factors are associated with the public use. Intention is the most powerful aspect for daily mode choice as a habitual behavior. Abstract: While parents are the ultimate decision makers for their children's mode of transport when commuting to school, their own travel mode choice is also under the influence of their children's trip requirements. This study proposes a model to forecast the behaviour of parents and children in choice of public transport for trips to school and work. A sample of 4000 households, in which 1876 responded (return rate 47.4%), was surveyed using paper questionnaires. Respondents had at least one child at primary school. Descriptive statistics showed that only 732 (39%) used public transport for commuting to work, of which 11% escorted their children to school three times a week or more, regardless of the mode of transportation used. A Structural equation model based on the theory of planned behaviour (TPB) was utilised to explain public transport (transit) use by parents and children. Results emphasised the intentional aspect of transit use. TPB factors (perceived behavioural control and intention), habit, situational variables (access to public transport infrastructure) and related variables of school journeys (perceived distance to school, escorting children) were found to be associated with type of transportation.